2020
DOI: 10.1038/s41598-020-79221-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the release of nickel and titanium under orthodontic treatment

Abstract: The metal alloys used in dentistry are made mainly of nickel (Ni), titanium (Ti), and other elements such as molybdenum (Mo), zirconium (Zr), iron (Fe), tin (Sn), chrome (Cr), carbon (C), copper (Cu) and niobium (Nb) which can release metal ions in unstable environments. The aim of this work was determine the salivary pH before and during orthodontic treatment; evaluate the release of metal ions, mainly Ni and Ti, in urine and saliva using Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES); and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…In view of the fact that metallic orthodontic appliances are still in active use, this represents an opportunity to study changes in oral tissue developing in patients undergoing orthodontic treatment, considering that the treatment periods are often lengthy. Most of the materials used in orthodontics are made of stainless steel, which contains chrome and iron; these metals have been associated with DNA damage due to corrosive effects [13,14]. Among the components of the alloys present in metallic materials, previous studies have indicated that nickel (Ni) is potentially the most damaging in terms of cytotoxicity [6,7,9,[15][16][17], allergy [18][19][20][21], mutagenesis [6,17,22] and/ or bioaccumulation [16][17][18]21].…”
Section: Discussionmentioning
confidence: 99%
“…In view of the fact that metallic orthodontic appliances are still in active use, this represents an opportunity to study changes in oral tissue developing in patients undergoing orthodontic treatment, considering that the treatment periods are often lengthy. Most of the materials used in orthodontics are made of stainless steel, which contains chrome and iron; these metals have been associated with DNA damage due to corrosive effects [13,14]. Among the components of the alloys present in metallic materials, previous studies have indicated that nickel (Ni) is potentially the most damaging in terms of cytotoxicity [6,7,9,[15][16][17], allergy [18][19][20][21], mutagenesis [6,17,22] and/ or bioaccumulation [16][17][18]21].…”
Section: Discussionmentioning
confidence: 99%
“…Oral cavity diseases may be developed as a result of changes in the oral fluid characteristics, including pH, which can modify the properties of dental materials [ 1 , 44 , 45 , 46 ]. Other researchers have highlighted the correlation between salivary pH and changes in the characteristics of tooth structure and in the restorative dental materials [ 42 , 43 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, NiTi or SS archwires are used simultaneously with the studied components [2] and may contribute with more metal release into the oral cavity [39]. In a recent study [63], other authors found a significant increase in Ni concentration in the urine of patients undergoing orthodontic treatment, encouraging further research on bioaccumulation of this metal. Orthodontic appliances may be an additional source of potentially toxic elements that should not be disregarded [39], particularly for patients hypersensitive to Ni.…”
Section: Orthodontic Componentsmentioning
confidence: 99%